FOSTERING CREATIVITY AND CRITICAL THINKING IN THE CLASSROOM ("Conference on Universal Science Research 2023", 2024)
This article explores strategies for promoting creativity and critical thinking in the classroom, emphasizing the importance of student-centered approaches and fostering an environment that encourages exploration, inquiry, and innovation.